(untitled) (Contemporary Journal of Social Science Review, 2025)
The river system in Pakistan, mainly the Indus River and its affiliated tributaries, is therefore of significant importance in the support of agriculture, the economy, and holding off a rich system of biological resources. This paper provides a detailed geographical review of the rivers of Pakistan with a focus on their hydrology and role in ecology. The research adopts secondary research using published sources, hydrological studies, climate analysis, and governmental data sources for measures of river condition and climate change effects. Secondary data related to climate include the Pakistan Meteorological Department (PMD), reports of NASA, IPCC, selected articles, and institutional publications. The effects of climate change are analyzed throughout the paper through glacier shrinkage, changes in precipitation, and consequences for water availability, crop production, and floods. They also examine feedback mechanisms through which climate change includes enhancing the existing human feedbacks like deforestation and construction of dams. In doing so, this paper synthesizes GIS mapping technology with climate modeling to explore the spatial distribution of climate impacts and interpolate the potential vulnerability of specific areas. As such, the present study reveals the importance of effective and sustainable water management policies, ecosystem recovery, and adaptation to cope with climate change impacts on rivers and the associated population in Pakistan.